2018
DOI: 10.1515/sjpain-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the relationships among race, prayer, and pain

Abstract: Abstract Background and aims Compared to White individuals, Black individuals demonstrate a lower pain tolerance. Research suggests that differences in pain coping strategies, such as prayer, may mediate this race difference. However, previous research has been cross-sectional and has not determined whether prayer in and of itself or rather the passive nature of prayer is driving the effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 74 publications
1
28
0
Order By: Relevance
“…This consideration is important because not only can the type, frequency, or combination thereof influence the analgesic effect, but also because conditions such as central sensitivity may impact the strategy’s efficacy/perceived efficacy. While the current sample was too small to investigate this relationship, prior studies observing in vivo coping using active and passive prayer and experimental pain sensitivity found that the active prayer group displayed higher cold pain tolerance than passive and no prayer groups (43). Similarly, in our study, in vivo passive coping was associated with SM use in NHBs, who typically use prayer at greater rates than NHWs (44).…”
Section: Discussionmentioning
confidence: 80%
“…This consideration is important because not only can the type, frequency, or combination thereof influence the analgesic effect, but also because conditions such as central sensitivity may impact the strategy’s efficacy/perceived efficacy. While the current sample was too small to investigate this relationship, prior studies observing in vivo coping using active and passive prayer and experimental pain sensitivity found that the active prayer group displayed higher cold pain tolerance than passive and no prayer groups (43). Similarly, in our study, in vivo passive coping was associated with SM use in NHBs, who typically use prayer at greater rates than NHWs (44).…”
Section: Discussionmentioning
confidence: 80%
“… 15 Pain catastrophizing, defined as a negative emotional and cognitive response to pain, has also been identified as a potential mechanism by which different racial groups respond to pain. 54 , 55 Further, NHBs more frequently endorse the use of hoping, praying, and diverting attention as primary coping strategies for pain, 56 , 57 effects which partially account for adverse pain outcomes among this group. 58 …”
Section: Discussionmentioning
confidence: 99%
“…Journal of Pain Research 2021:14 pain, 56,57 effects which partially account for adverse pain outcomes among this group. 58 Despite similar levels of gratitude and trait resilience across NHBs and NHWs, our results suggest that these resilience factors are differentially associated with painrelated outcomes across racial groups.…”
Section: Dovepressmentioning
confidence: 99%
“…As physical quality of life is significantly correlated with illness and/or advanced age, this may be related to the participants in this study being predominantly young and physically fit. The benefits of religion on subjective health seem to be greatest for those suffering from physical health problems (Meints et al, 2018). Koenig (2001) and Seeman et al (2003) found physical benefits from religiosity, as it is associated with better lipid profiles, lower blood pressure, better immune function and decreased levels of cortisol.…”
Section: Discussionmentioning
confidence: 99%